Clinical characterization of respiratory large droplet production during common airway procedures using high-speed imaging - Müller, Sarina Katrin; Veltrup, Reinhard; Jakubaß, Bernhard; Kniesburges, Stefan; Hübner, Matthias; Kempfle, J. S.; Dittrich, Sven; Dittrich, Sven; Iro, Heinrich; Döllinger, Michael (Scientific Reports, 2021)
During the COVID-19 pandemic, a significant number of healthcare workers have been infected with SARS-CoV-2. However, there remains little knowledge regarding large droplet dissemination during airway management procedures in real life settings. 12 different airway management procedures were investigated during routine clinical care. A high-speed video camera (1000 frames/second) was for imaging. Quantitative droplet characteristics as size, distance traveled, and velocity were computed. Droplets were detected in 8/12 procedures. The droplet trajectories could be divided into two distinctive patterns (type 1/2). Type 1 represented a ballistic trajectory with higher speed large droplets whereas type 2 represented a random trajectory of slower particles that persisted longer in air. The use of tracheal cannula filters reduced the amount of droplets. Respiratory droplet patterns generated during airway management procedures follow two distinctive trajectories based on the influence of aerodynamic forces. Speaking and coughing produce more droplets than non-invasive ventilation therapy confirming these behaviors as exposure risks. Even large droplets may exhibit patterns resembling the fluid dynamics smaller airborne aerosols that follow the airflow convectively and may place the healthcare provider at risk.
CRIS-Team Scopus Importer:2021-06-04

Effects of surgical masks on aerosol dispersion in professional singing - Kniesburges, Stefan; Schlegel, Patrick; Peters, Gregor; Westphalen, Caroline; Jakubaß, Bernhard; Veltrup, Reinhard; Kist, Andreas; Döllinger, Michael; Gantner, Sophia; Kuranova, Liudmila; Benthaus, Tobias; Semmler, Marion; et al. (Journal of Exposure Science and Environmental Epidemiology, 2021)
Background In the CoVID-19 pandemic, singing came into focus as a high-risk activity for the infection with airborne viruses and was therefore forbidden by many governmental administrations. Objective The aim of this study is to investigate the effectiveness of surgical masks regarding the spatial and temporal dispersion of aerosol and droplets during professional singing. Methods Ten professional singers performed a passage of the Ludwig van Beethoven's "Ode of Joy" in two experimental setups-each with and without surgical masks. First, they sang with previously inhaled vapor of e-cigarettes. The emitted cloud was recorded by three cameras to measure its dispersion dynamics. Secondly, the naturally expelled larger droplets were illuminated by a laser light sheet and recorded by a high-speed camera. Results The exhaled vapor aerosols were decelerated and deflected by the mask and stayed in the singer's near-field around and above their heads. In contrast, without mask, the aerosols spread widely reaching distances up to 1.3 m. The larger droplets were reduced by up to 86% with a surgical mask worn. Significance The study shows that surgical masks display an effective tool to reduce the range of aerosol dispersion during singing. In combination with an appropriate aeration strategy for aerosol removal, choir singers could be positioned in a more compact assembly without contaminating neighboring singers all singers.
CRIS-Team WoS Importer:2021-10-15

Evaluation of Respiratory Particle Emission during Otorhinolaryngological Procedures in the Context of the SARS-CoV-2 Pandemic - Veltrup, Reinhard; Kniesburges, Stefan; Döllinger, Michael; Falk, Sebastian; Müller, Sarina Katrin (Diagnostics, 2022)
Understanding the risk of infection by routine medical examination is important for the protection of the medical personnel. In this study we investigated respiratory particles emitted by patients during routine otolaryngologic procedures and assessed the risks for the performing physician. We developed two experimental setups to measure aerosol and droplet emission during rigid/flexible laryngoscopy, rhinoscopy, pharyngoscopy, otoscopy, sonography and patient interview for subjects with and without masks. A high-speed-camera setup was used to detect ballistic droplets (approx. > 100 µm) and an aerosol-particle-sizer was used to detect aerosol particles in the range of 0.3 µm to 10 µm. Aerosol particle counts were highly increased for coughing and slightly increased for heavy breathing in subjects without masks. The highest aerosol particle counts occurred during rigid laryngoscopy. During laryngoscopy and rhinoscopy, the examiner was exposed to increased particle emission due to close proximity to the patient’s face and provoked events such as coughing. However, even during sonography or otoscopy without a mask, aerosol particles were expelled close to the examiner. The physician’s exposure to respiratory particles can be reduced by deliberate choice of examination technique depending on medical indication and the use of appropriate equipment for the examiners and the patients (e.g., FFP2 masks for both).
CRIS-Team Scopus Importer:2022-07-15
Keywords: face masks; high-speed visualization; laryngoscopy; optical particle sizer; otoscopy; pharyngoscopy; respiratory particles; rhinoscopy; SARS-CoV-2; sonography

Fireflies: Photorealistic Simulation and Optimization of Structured Light Endoscopy - Henningson, Jann-Ole; Veltrup, Reinhard; Semmler, Marion; Döllinger, Michael; Stamminger, Marc (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2024)
There exist various approaches for the 3D reconstruction of dynamic scenes. In medicine, particularly in endoscopy, single-shot structured light systems are frequently explored, as they allow for the reconstruction of dynamic, feature-less surfaces. Design and manufacturing of structured light endoscopes, however, implies high initial costs that significantly hinder the availability and development of these systems. To streamline this process, simulation systems are necessary that allow researchers to not only model the intricacies of medical domains, but also of structured light systems themselves. To address this, we propose Fireflies, a differentiable framework for the physically-based simulation and domain randomization of structured light endoscopy. Based on the differentiable Mitsuba renderer, Fireflies facilitates and simplifies the development of domain-specific algorithms for endoscopic procedures. In this paper, we demonstrate the effectiveness of our framework by jointly optimizing domain-specific laser-based projection pattern for Structured Light Endoscopy, and generating large-scale synthetic training data for efficient supervised learning without manual labeling. We show that a) an optimized projection pattern can increase the reconstructability of a target domain and b) the synthetic data generated by Fireflies lowers the labeling effort required for endoscopic machine learning tasks. The source code is available at: https://github.com/Henningson/Fireflies
CRIS-Team Scopus Importer:2024-11-01
Keywords: Differentiable Rendering; Domain Randomization; Endoscopy; Simulation; Structured Light

Impulse dispersion of aerosols during playing wind instruments - Gantner, Sophia; Echternach, Matthias; Veltrup, Reinhard; Westphalen, Caroline; Köberlein, Marie Christine; Kuranova, Liudmila; Peters, Gregor; Jakubaß, Bernhard; Benthaus, Tobias; Döllinger, Michael; Kniesburges, Stefan (PLoS ONE, 2022)
Musical activities, especially singing and playing wind instruments, have been singled out as potentially high-risk activities for the transmission of SARS CoV-2, due to a higher rate of aerosol production and emission. Playing wind instruments can produce condensation, droplets of saliva, and aerosol particles, which hover and spread in the environmental air's convectional flows and which can be potentially infectious. The aim of this study is to investigate the primary impulse dispersion of aerosols that takes place during the playing of different wind instruments as compared to breathing and to speaking. Nine professional musicians (3 trumpeters, 3 flautists and 3 clarinetists) from the Bavarian Symphony Orchestra performed the main theme from the 4th movement of Ludwig van Beethoven's 9th symphony in different pitches and loudness. The inhaled air volume was marked with small aerosol particles produced using a commercial e-cigarette. The expelled aerosol cloud was recorded by cameras from different perspectives. Afterwards, the dimensions and dynamics of the aerosol cloud were measured by segmenting the video footage at every time point. Overall, the flutes produced the largest dispersion at the end of the task, reaching maximum forward distances of 1.88 m. An expulsion of aerosol was observed in different directions: Upwards and downwards at the mouthpiece, at the end of the instrument, and along the flute at the key plane. In comparison, the maximum impulse dispersions generated by the trumpets and clarinets were lower in frontal and lateral direction (1.2 m and 1.0 m towards the front, respectively). Also, the expulsion to the sides was lower.
CRIS-Team Scopus Importer:2022-03-11

Influence of Perspective Distortion in Laryngoscopy - Veltrup, Reinhard; Kniesburges, Stefan; Semmler, Marion (Journal of Speech Language and Hearing Research, 2023)
OBJECTIVE: An experiment with controllable boundaries was designed to assess the influence of the recording angle and distance on two-dimensional (2D) imaging in laryngoscopy and resulting 2D parameter calculation derived from the glottal area waveform (GAW). METHOD: Two high-speed camera setups were used to synchronously record an oscillating synthetic vocal fold (VF) model, simulating a high-speed videoendoscopy. One camera recorded at variable lateral recording angles and a reference camera in superior perspective. This was performed at different physiological recording distances and for two oscillation modes (with/without contacting VFs). The GAW was derived from the segmented glottis, and two parameters each for the categories of symmetry, periodicity, and closure were calculated, as well as two derivative measures. The percentage difference between the variable and reference camera value pairs was calculated, and the angle and height dependencies were quantified using linear regression. RESULTS: The visual perception of a laryngoscopy was found to be influenced by the lateral recording angle, which may lead to misinterpretation of VF symmetry among inexperienced observers. The strongest influence of recording angle was observed for symmetry parameters, the strongest being the Amplitude Symmetry Index with up to 2.6%/° (p < .05). A dependence on the recording distance was only found for the Maximum Area Declination Rate. CONCLUSIONS: The recording angle in 2D laryngoscopy should be carefully considered during visual inspection of the VF dynamics. Most of the investigated objective parameters were unaffected by the examined perspective distortion. However, especially left-right symmetry measures should only be used under controlled boundary conditions to avoid misdiagnosis and misinterpretation. SUPPLEMENTAL MATERIAL: https://doi.org/10.23641/asha.23961183.
CRIS-Team Scopus Importer:2023-09-22

Modeling the pre-phonatory vocal fold posture in the larynx model SynthVOICE - Kniesburges, Stefan; Veltrup, Reinhard; Fattoum, Sahar; Schützenberger, Anne (Proceedings of the International Congress on Acoustics, 2019)
This work presents a synthetic larynx model that includes the adduction motion and the elongation of the vocal folds. Beside the description of the model, validation measurements and their results will be presented.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Fluid-structure interaction; Phonation; Synthetic larynx model

Sources of Aerosol Dispersion During Singing and Potential Safety Procedures for Singers - Westphalen, Caroline; Kniesburges, Stefan; Veltrup, Reinhard; Gantner, Sophia; Peters, Gregor; Benthaus, Tobias; Jakubaß, Bernhard; Köberlein, Marie; Döllinger, Michael; Echternach, Matthias (Journal of Voice, 2021)
Introduction: With respect to the Covid-19 pandemic, singing is assumed to be associated with a high potential person-to-person transmission. However, it remains unclear how the impulse dispersion varies with different types of articulation, intensity levels of diction, or body position. Furthermore, it has not been understood in detail how to prevent aerosol dispersion during singing. Material and Methods: Single professional singers from the Bavarian Radio Chorus were asked to sing in different head positions, with different articulation patterns and different masks after inhaling the basic liquid of an e-cigarette. The vapor cloud was segmented and tracked over time. Results: Consonants and exaggeration of diction enhanced the distance reached by the impulse dispersion. Furthermore, the greatest dispersion was reached for a neutral head position. All protection masks stopped the initial jet of the aerosols but the FFP2 masks were the most effective. Conclusion: Some protection equipment has been identified to be promising in reducing aerosol dispersion. However, systematic effects have to be evaluated in greater collectives.
CRIS-Team Scopus Importer:2021-04-19
Keywords: SingErs—AeroSols—COVID-19

Synchronous 3D Imaging of the Medial and Superior Vocal Fold Surface in an excised human Hemilarynx - Veltrup, Reinhard; Angerer, Susanne; Geßner, Elena; Matheis, Friederike; Sümmerer, Emily; Döllinger, Michael; Semmler, Marion (IEEE Transactions on Biomedical Engineering, 2024)
Objective: This study investigates relationships between the oscillation behavior of the medial and superior vocal fold (VF) surfaces during sustained phonation in a human cadaver hemilarynx. Methods: An experimental test stand synchronously captured the medial and superior VF surfaces of a human ex vivo hemilarynx during sustained phonation using two high-speed camera setups in 24 experimental settings. The 3D coordinates of the medial VF surface were reconstructed by triangulation of sewn-in marker points, while laser-based reconstruction was used for the superior VF surface. Correlation analysis and linear regression were used to quantify the connections of the mean and maximal vertical and lateral VF displacements and the VF velocities. Additionally, stepwise linear regression was used to analyze the impact of the measurement variables mean flow rate, adduction and elongation. Results: Strong linear relationships between all of the tested corresponding parameter pairs of the superior and medial VF surfaces were found (p<.001). Mean and maximum vertical displacements of the medial surface were both approximately 50% of the superior surface. The mean lateral displacements for the medial surface were 12% below the superior surface but 12% higher for the maximum values. The mean and maximum VF velocities were 32% and 36% lower for the medial surface. Conclusion: The suggested multi-modal test stand allows efficient, comprehensive analysis of human hemilarynges and provides promising information about the interaction of the different VF areas and opens up the systematic analysis of multiple hemilarynges. Significance: In future, our results could integrate into ENT diagnostics using 3D laryngoscopy where the hidden medial VF surface dynamics may be predicted from the observable superior surface.
CRIS-Team Scopus Importer:2024-09-20
Keywords: 3D Reconstruction; Hemilarynx; Synchronous High-Speed Imaging; Vocal Fold Dynamics

Three-Dimensional Analysis of Vocal Fold Oscillations: Correlating Superior and Medial Surface Dynamics Using Ex Vivo Human Hemilarynges - Veltrup, Reinhard; Angerer, Susanne; Geßner, Elena; Matheis, Friederike; Sümmerer, Emily; Henningson, Jann-Ole; Döllinger, Michael; Semmler, Marion (Bioengineering, 2024)
The primary acoustic signal of the voice is generated by the complex oscillation of the vocal folds (VFs), whereby physicians can barely examine the medial VF surface due to its anatomical inaccessibility. In this study, we investigated possibilities to infer medial surface dynamics by analyzing correlations in the oscillatory behavior of the superior and medial VF surfaces of four human hemilarynges, each in 24 different combinations of flow rate, VF adduction, and elongation. The two surfaces were recorded synchronously during sustained phonation using two high-speed camera setups and were subsequently 3D-reconstructed. The 3D surface parameters of mean and maximum velocities and displacements and general phonation parameters were calculated. The VF oscillations were also analyzed using empirical eigenfunctions (EEFs) and mucosal wave propagation, calculated from medial surface trajectories. Strong linear correlations were found between the 3D parameters of the superior and medial VF surfaces, ranging from 0.8 to 0.95. The linear regressions showed similar values for the maximum velocities at all hemilarynges (0.69–0.9), indicating the most promising parameter for predicting the medial surface. Since excessive VF velocities are suspected to cause phono-trauma and VF polyps, this parameter could provide added value to laryngeal diagnostics in the future.
CRIS-Team Scopus Importer:2024-11-08
Keywords: 3D laryngoscopy; empirical eigenfunctions; hemilarynx; high-speed imaging; laryngeal modeling; mucosal wave propagation; vocal folds